Experimental verification of the effectiveness of pedagogical conditions for the formation of a culture of morally effective relations in future managers of foreign economic activity (Pedagogy of Higher and Secondary Education, 2011)
The article describes the effectiveness of pedagogical conditions proposed for the formation of culture of moral-business relations of future international managers.
Keywords: pedagogical conditions; forming experiment; complex program; special course “Moral-business culture of a manager”; control and experimental groups